Different developmental environments reveal multitrait plastic responses in South American Anostomidae fish. Issue 7 (10th October 2019) - Bonini‐Campos, Bianca; Lofeu, Leandro; Brandt, Renata; Kohlsdorf, Tiana
Abstract: Complex phenotypes result from developmental processes integrating genetic, epigenetic, and environmental information. Although changing environments combine several signals that may induce multitrait plastic responses, literature often decodes developmental plasticity into single trait variation as a function of isolated environmental signals. To address the multivariate nature of developmental plasticity, we evaluated how different combinations of environmental signals influence the development of morphological and behavioral traits. We raised Megaleporinus macrocephalus (Anostomidae) in four different developmental environments, and found that foraging position and structural complexity during development induced different morphotypes, which overlapped with behavioral patterns. Foraging position induced distinct patterns of mouth and fin positioning and overall body shape, which were accentuated by structural complexity. Moreover, fish most often chose conditions similar to their developmental environments. Combined signals during development, therefore, revealed environment‐specific phenotypic patterns associating morphology and behavior. Such results endorse the ability of developmental processes to influence the variation present in natural populations. Implications of addressing the multivariate essence of developmental plasticity transcend the evolutionary theory and inspire applications in several fields. Abstract : Signals from different developmental environments induced plastic responses in the fish M. macrocephalus, and specific combinations of foraging position and structural complexity elicited phenotypic responses that integrate morphology and behavior. Research Highlights: Integrated phenotypic responses arise from particular combinations of environmental signals. Plastic responses encompass concomitant and correlated changes. Environmental signals bias the development of morphological and behavioral traits in fish.